Degassing effect on nickel aluminum bronze alloy castings - Kavinmugil, Kalaiselvan (2022)
Copper was used years ago as basic processing material and engineering used. Copper was choosing because it offers shaping flexibility, low melting point and also alloying capability to achieved selected properties such as corrosion resistance. One of selected copper alloy in engineering usage is Nickel Aluminum Bronze (NAB). The composition of NAB was prepared by mixed of several elements addition during furnace melting. During solidification, to prevent gas residue which probably reside inside its alloy microstructure, a degassing agent must be added. So, molten metal was poured into the sand cast mould with a different combination of degassing volume. Later the melt was let solidified towards room temperature. The effect of degassing volume on the composition addition of NAB was studied. The results show that degassing influence directly the solidification cooling curve, microstructure and mechanical properties. All samples show degassing volume influenced the solidification temperature point namely liquidus arrest (TAL), eutectic nucleation (TES), undercooling (TEU), recalescence (TER) and point of eutectic stop (TEE). Between 0.5 to 1.1% addition of degassing agent, each of temperature point drop around 9 to 11o Celsius. Increasing degassing volume generally decreasing the solidification temperature point. The fall of the temperature will encourage the changes of composition’s microstructure and its shape after solidification phase was finished. Most of the microstructure shape, size and its distribution evaluation was studied by means of Scanning Electron Microscope (SEM). SEM reveal the Dendritic Arm Spacing (DAS) and its secondary (SDAS) branch. Between 0.5 to 1.1% addition of degassing agent, each of the DAS and SDAS dropped from 263 µm to 165µm, and 45 to 40 µm respectively. The lower the solidification temperature, the smaller the DAS and SDAS morphology due to a lesser time for its growth phase. Less time permit limitation for grain size to evolve. Experimental works showed the degassing agent addition up to 1.1% increased the tensile and hardness value as well. The result from this experimental works suggested the mechanical properties of composition addition depended on its microstructure morphology. This phenomenon is directly influenced by solidification that affected by the degassing addition.